A new combination of cyclohexylhydrazine and IBX for oxidative generation of cyclohexyl free radical and related synthesis of parvaquone. Issue 19 (10th May 2017) - Patil, Pravin C.; Akamanchi, Krishnacharya G.
Graphical abstract: Highlights: New method of generating cyclohexyl radical by using IBX and cyclohexylhydrazine. Parvaquone synthesized in 60% yield using metal, hazardous peroxide free conditions. Described method has advantages of single step and mild reaction conditions. The mechanism for cyclohexyl radical mediated synthesis of parvaquone is postulated. Abstract: The present paper demonstrates a single-step and straightforward synthesis of parvaquone through intermediacy of cyclohexyl radical generated from novel combination of cyclohexylhydrazine and o -iodoxybenzoic acid and subsequently trapped by 2-hydroxy-1, 4-naphthoquinone. Formation of cyclohexyl free radical using this new combination was reaffirmed by cyclohexylation of readily available 2-amino-1, 4-naphthoquinone.